Revision of the Patagonian Iguanids of the Liolaemus elongatus Complex - Cei, José Miguel Alfredo María (1974)
Patagonian lizards of the Liolaemus elongatus complex are revised. The proposed taxonomic arrangement consists of the widespread subandean L. elongatus elongatus (Koslowsky) between 33° and 45° south latitude, L. elongatus petrophilus Donoso B. and Cei from Central Rio Negro uplands and Northern Chubut, and a new allosympatric, closely related form, L. austromendocinus sp.nov., here described, from southern Mendoza Province, Argentina. Geographical variation and clinal trends of L. elongatus elongatus are analyzed and discussed. Sympatry and serological relationships of L. elongatus elongatus and L. austromendocinus north of the Barrancas-Colorado river are reported and criticized.